Kendo & Shodo in Life: A Long-lasting Association Between the Way of the Sword and the Brush (Revista de Artes Marciales Asiáticas, 2012)
For half of my life, I have been well supported by following two Japanese traditional “ways” that have always kept me on the right track. I would like to explain how these two “ways,” or do as they are called in Japanese, have allowed me to maintain my Japanese identity even though I live far from Japan. One is shodo (Japanese calligraphy) and the other is kendo (a Japanese sword art). This short article presents my experience with the “way” of shodo and kendo, which in turn may enrich your own martial studies.